APHRODISIAC ACTIVITY OF CYCAS CIRCINALIS.L AND IONIDIUM SUFFRUTICOSUM.GING ON MALE WISTER ALBINO RATS - KUMAR, B. SENTHIL; KUMAR, J. VIJAYA; SELVARAJ , R. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Introduction: Cycas circinalis .L and Ionidium suffruticosum. Ging are the two herbs used in Siddha system of medicine (Indian Medicine) for years together to improve the fertility of male. Objective: The aphrodisiac activities of the two herbs Cycas circinalis .L and Ionidium suffruticosum. Ging were tested on male albino rats and compared the effect with normal and positive control male albino rats. Materials and Methods: The present study involves 4 groups, each group has 6 healthy sexually active male albino rats. The Cycas circinalis and Ionidium suffruticosum extract (200mg/kg body weight) were administered orally to 2 experimental group of albino rats and its sexual performance was compared to the normal albino rats (given normal saline) and positive control albino rats (given Sildenafil citrate 4.5mg/kg body weight). The aphrodisiac activities of rats due to the effect of the herb were observed by various parameters such as mount frequency, mount latency, intromission frequency, intromission latency, ejaculation latency, post ejaculatory Interval and total sexual behavior. The data's were analyzed using one way ANOVA and found to be statistically significant. Results: The herbs showed significant positive results in improving various parameters involved in maintaining maleness. The study proves that Cycas circinalis and Ionidium suffruticosum both have aphrodisiac activity and Ionidium suffruticosum was proved to be more effective and almost has the similar effect of Sildenafil citrate. Conclusion The herbal extracts possessing aphrodisiac activity will be of great use for males suffering from sexual disorders like impotence. KEYWORDS: Ionidium suffruticosum, Cycas circinalis, Aphrodisiac activity, Mount frequency, Mount latency, Intromission frequency, Intromission latency, Ejaculation latency, Post ejaculatory interval, Total sexual behavior.